2019
DOI: 10.1111/syen.12401
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA evolution provides new evidence for a close relationship of Diplura to Insecta

Abstract: The phylogenetic interrelationships among four hexapod lineages (Protura, Collembola, Diplura and Insecta) are pivotal to understanding the origin of insects and the early diversification of Hexapoda, but they have been difficult to clarify based on the available data. In this study, we identified 91 conserved microRNA (miRNA) families from 36 panarthropod taxa, including seven newly sequenced non‐insect hexapods. We found major clade differentiation accompanied by the origin of novel miRNA families, and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…The evolutionary divergence of miRNAs may contribute to the diversification of species (Plasterk, 2006 ). Liu et al ( 2020 ) analysed the miRNA data of FCDK based on genome data reported in this study and small RNA (sRNA) data from mixed embryos, juveniles and adults (GenBank accession no. SRP132383).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The evolutionary divergence of miRNAs may contribute to the diversification of species (Plasterk, 2006 ). Liu et al ( 2020 ) analysed the miRNA data of FCDK based on genome data reported in this study and small RNA (sRNA) data from mixed embryos, juveniles and adults (GenBank accession no. SRP132383).…”
Section: Methodsmentioning
confidence: 99%
“…SRP308782). Based on the sRNA data and chromosomal‐level genome assemblies of FCDK and FCSH, known miRNAs with homologous genes in the miRBase 21 database (Kozomara & Griffiths‐Jones, 2014 ) were identified, and novel miRNAs were predicted according to the procedure described in Liu et al ( 2020 ). By mapping miRNA precursors to the corresponding genome using mapchart (Voorrips, 2002 ), the locations of miRNAs were recorded and compared between FCDK and FCSH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processed reads were compared to the Rfam [119] database using bowtie (v1.3.0) [120] to remove rRNA, tRNA, and snRNA (bowtie -f -a --best --strata -p --al --un). Bowtie was then used to identify miRNAs, with the reference sequence as the miRNA hairpin sequence of L. migratoria [121][122][123]. The remaining small RNAs were mapped to TEs and TE transcripts, of which 23-31nt aligned reads were considered TE-derived piRNAs [97,124] ( bowtie -v 3 -a reads.fa -S --al --un -f).…”
Section: Te-derived Pirnas Identificationmentioning
confidence: 99%